Establishment of National Standards Bureaux in Dominica and St. Kitts and Nevis : final report June 1996 - Rhynd, Dudley B. ([CCS] [Georgetown]GY, 1996)
Provides short and long term plans, as well as options for determining the type of standards body to be established. Presents operational guidelines for establishing the standards bodies.